Sodium–glucose co‐transporter 2 inhibitors in heart failure: beyond glycaemic control. A position paper of the Heart Failure Association of the European Society of Cardiology. (5th August 2020) - Seferović, Petar M.; Fragasso, Gabriele; Petrie, Mark; Mullens, Wilfried; Ferrari, Roberto; Thum, Thomas; Bauersachs, Johann; Anker, Stefan D.; Ray, Robin; Çavuşoğlu, Yuksel; Polovina, Marija; Metra, Marco; et al.
Abstract : Heart failure (HF) is common and associated with a poor prognosis, despite advances in treatment. Over the last decade cardiovascular outcome trials with sodium–glucose co‐transporter 2 (SGLT2) inhibitors in patients with type 2 diabetes mellitus have demonstrated beneficial effects for three SGLT2 inhibitors (empagliflozin, canagliflozin and dapagliflozin) in reducing hospitalisations for HF. More recently, dapagliflozin reduced the risk of worsening HF or death from cardiovascular causes in patients with chronic HF with reduced left ventricular ejection fraction, with or without type 2 diabetes mellitus. A number of additional trials in HF patients with reduced and/or preserved left ventricular ejection fraction are ongoing and/or about to be reported. The present position paper summarises recent clinical trial evidence and discusses the role of SGLT2 inhibitors in the treatment of HF, pending the results of ongoing trials in different populations of patients with HF.